MARKETING APPROACHES FOR EFFECTIVE MUSEUM MANAGEMENT - Serafimova, Vesela; Filipova, Milena (Annals of Spiru Haret University. Economic Series, 2024)
When it comes to effective museum management, implementing smart marketing approaches is crucial for attracting visitors, engaging with the community, and ensuring long-term sustainability. Some key marketing activities can be highlighted for a successful museum management: targeted audience segmentation; compelling branding; engaging content marketing techniques; collaborations and partnerships; the application of specific principles for digital marketing and promotion of a strong online presence; community engagement; visitor experience enhancement; membership programs and loyalty benefits implementation; data analytics and continuous evaluation and adaptation. By implementing these marketing approaches, museums can effectively promote their collections, engage with diverse audiences, and secure their long-term success. Museum management involves overseeing all aspects of a museum’s operations, including administration, collections management, exhibition planning, educational programs, marketing, fundraising, and visitor services. The present paper approaches different marketing instruments that can effectively enhance the efficiency of museums activity and shows a practical example regarding „Alexei Rilets” Museum from Rila. Overall, effective museum management requires a combination of leadership, strategic planning, financial acumen, creativity, and a deep passion for preserving and sharing cultural heritage. By managing these various aspects, museum managers can nurture vibrant institutions that educate, inspire, and engage audiences from all walks of life.